Platelet Adhesion to Collagen Type I, Collagen Type IV, von Willebrand Factor, Fibronectin, Laminin and Fibrinogen: Rapid Kinetics under Shear - Polanowska-Grabowska, Renata; Simon, Carl G., Jr.; Gear, Adrian R. L. (Thrombosis and Haemostasis, 1999)
Extracellular matrix proteins in the blood vessel wall fulfill an essential role in haemostasis by promoting platelet adhesion at the site of vessel injury. We have combined a continuous-flow system with affinity chromatography to study platelet adhesion under conditions mimicking arterial flow and have examined the adhesion kinetics of unstimulated platelets to collagens type I and IV, von Willebrand factor (vWf), fibronectin, laminin and to fibrinogen. In the absence of red cells, in ACD-prepared plasma adhesion to collagens type I and IV or vWf was rapid, efficient (>50% in <1 s ) and independent of shear rates from 650 to 3400 s-1with kinetics following an inverse exponential decay curve. We introduced a simple mathematical model in which this type of kinetics arises, and which may be more generally applicable to various adhesion processes under flow conditions. The model is characterized by the rate of platelet deposition on the adhesive surface being proportional to the number of platelets in the flow. Adhesion to fibronectin was independent of shear rate, but revealed a lag phase of ~1.5 s before significant adhesion began. Laminin and fibrinogen supported efficient adhesion at low shear rates (650-1000 s-1), but a lag phase of ~1.5 s was seen at high shear rates (1700-3400 s-1). Control proteins (albumin and gelatin) supported minimal adhesion. Nonspecific adhesion to poly-l-lysine differed from that to other substrate proteins in that the kinetics were linear. In conclusion, human platelets adhered specifically, rapidly (within seconds) and efficiently to several proteins under flow conditions and the kinetics of adhesion depended on the protein serving as substrate as well as on shear rate.